Investigation of heat capacity in Nb doped nickel oxide. (2022) - Parwani, Suraj; Dixit, R.C.; Choudhary, K.K.; Kaurav, Netram
Abstract: Nickel oxide (NiO) is one of the most important transition metal oxides, whose properties are very suitable for solar cells, smart windows, gas sensing. Further, it exhibits semiconducting properties and becomes more conducting by doping with other atoms. Therefore, in the present investigation we have altered the transport properties of NiO by doping of another transition or metallic element in stoichiometric ratio. Samples were prepared by following the solid-state process with different doping concentration of Nb element. These samples were characterized by X-ray diffraction. Heat capacity measurement was done by differential scanning calorimeter (DSC) and a clear anomaly in the vicinity of antiferromagnetic ordering were observed in all the samples.